2018
DOI: 10.1097/jsm.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Side Strain Has a High Incidence in First-Class Cricket Fast Bowlers in Australia and England

Abstract: Side strain is a common injury among first-class cricket fast bowlers, especially at younger ages. It was associated with the volume of first-class cricket played. Recurrence was common and occurred most frequently in the first 2 years after primary injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regarding the injured side, it has been reported that 78% of pitchers and 70% of fielders developed abdominal oblique muscle strain on the contralateral batting and pitching sides in MLB [5] . In Australian and English first-class cricket fast bowlers, the injured side of side strain of all 108 bowlers was reported to be the contralateral side [13] . Furthermore, in Australian first-class cricket fast bowlers, all 10 internal oblique muscle strains diagnosed by MRI were on the contralateral side [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the injured side, it has been reported that 78% of pitchers and 70% of fielders developed abdominal oblique muscle strain on the contralateral batting and pitching sides in MLB [5] . In Australian and English first-class cricket fast bowlers, the injured side of side strain of all 108 bowlers was reported to be the contralateral side [13] . Furthermore, in Australian first-class cricket fast bowlers, all 10 internal oblique muscle strains diagnosed by MRI were on the contralateral side [7] .…”
Section: Discussionmentioning
confidence: 99%
“…4 In Australian and English rst-class cricket fast bowlers, the injured side of side strain of all 108 bowlers was reported to be the contralateral side. 12 Furthermore, in Australian rst-class cricket fast bowlers, all 10 internal oblique muscle strains diagnosed by MRI were on the contralateral side. 6 A previous study that used electromyography to examine the activity of abdominal muscles during baseball pitching reported that the muscles on the contralateral side were more active than those on the dominant side.…”
Section: Discussionmentioning
confidence: 99%
“…Side strain is an injury to the lateral trunk that is reported in cricket fast bowlers [1][2][3][4] and baseball players. [5][6][7] It is an acute (usually) internal oblique muscle injury categorised as either a complete or partial tear of the muscle from the undersurface of one of the inferior ribs, most commonly from the 11th rib, then the 10th, 9th and 12th ribs.…”
Section: Introductionmentioning
confidence: 99%